Complejidad y delitos sistémicos - Orsi, Omar Gabriel (2019)
Despite technological advances and procedural reforms, the low efficiency of systemic crimes investigation -specially white collar crimes- could not be substantially improved. The work develops the potential of the complexity models, and formal methodologies for solving this kind of problems.